The Role of Internal Control Systems, Financial Literacy, and Technology Utilization on The Quality of Financial Reports In LPD Kintamani District - I Kadek Satria Rencana; Ni Luh Eka Ayu Permoni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the impact of internal control systems, financial literacy, and use of technology on the quality of financial reports in LPD Kintamani District. This study uses a quantitative approach. The data collection technique used in this study was in the form of a questionnaire given to the heads of LPDs in the Kintamani District. The data analysis technique used was SEM-PLS (Smart Equation Modeling- Partial Least Square) version 3.0 where the number of samples used in this study were 57 heads of LPD, determining the respondents using a purposive sampling technique. The results showed that the internal control system had a significant positive effect on the quality of the financial reports of the LPD in Kintamani District. Then Financial Literacy has a significant positive effect on the quality of financial reports at the LPD in Kintamani District. Furthermore, the use of technology has a positive and significant effect on the quality of financial reports at the LPD in Kintamani District